Scholar-activists in an expanding European food sovereignty movement. Issue 4 (7th June 2021) - Duncan, Jessica; Claeys, Priscilla; Rivera-Ferre, Marta G.; Oteros-Rozas, Elisa; Van Dyck, Barbara; Plank, Christina; Desmarais, Annette Aurélie
ABSTRACT: This article analyzes the roles, relations, and positions of scholar-activists in the European food sovereignty movement. In doing so, we document, make visible and question the political dimensions of researchers' participation in the movement. We argue that scholar-activists are part of the movement, but are distinct from the affected constituencies, put in place to ensure adequate representation of key movement actors. This is because scholar-activists lack a collective identity, have no processes to formulate collective demands, and no mechanisms for inter-researcher and researchers-movement communication. We reflect on whether and how scholar-activists could organize, and discuss possible pathways for a more cohesive and stronger researcher engagement in the movement.